Student Evaluations of Teaching as 'Fact-Totems': The Case of the UK National Student Survey. (November 2013) - Sabri, Duna
Taking the UK National Student Survey (NSS) as a case study of student evaluations of teaching (SET) which are now used widely in higher education, I argue that the production and consumption of such survey data have a symbolic value that exceeds, and is often independent of, any technical understanding of their statistical meaning. The NSS, in particular, has acquired significance that far outweighs its validity or intended use. This is evident in national policy where it has become the primary measure of 'the student experience', ostensibly articulating current students' views, and giving prospective students – as consumers – information to help them choose between courses. Higher education institutions now allocate resources to improving 'the student experience', as defined by NSS results. Their desire to improve NSS results has come to redefine higher education work and relationships between students and academics, academics and managers, and students and institutions. Moreover, NSS results and universities' relative positions in NSS scores have become 'fact-totems', a site of intense social attention within universities, provoking anticipatory anxiety, and becoming embedded in universities' identity narratives. Alongside an analysis of the policy structures that perpetuate the NSS at national and institutional levels, I draw on two studies conducted within one UK university to examine at a micro-level the meanings and practices that can be generated in the production and consumption of the NSS for students, academics and managers in higher education.